Atypical vulvar lipoma - A case report and literature review - Sadhvi Batra; Lindsey Nguy; Daniela Moino; Atousa Ordobazari; Mian M Shahzad (Elsevier, 2024)
Atypical spindle cell lipomatous tumors of the vulva are rare masses. We report a case of atypical spindle cell lipoma of the vulva and provide a succinct review of the current understanding of these benign masses. Specifically, this report describes a case of a 20-year-old nulligravid female who presented for evaluation of a labial mass that had been growing for one year. A pelvic MRI revealed a 7 cm fatty growth. The vulvar mass was surgically resected. This case report describes the pathologic staining pattern for these masses and reviews characteristics of these benign tumors such that they are not mistaken for malignancy.